Verkehrslenkung und -beschränkung. Rechtlich zulässige Handlungsmöglichkeiten der Luftreinhaltepolitik. - Lahl, Uwe; Steven, Wilhelm (Deutscher Verkehrs-Verl., 2005)
Zahlreiche Untersuchungen zeigen, dass Feinstaub (Partikeln - PM10) schwere Gesundheitsschäden und das Ansteigen der Sterblichkeitsrate auf Grund von Herz-Kreislauf-Erkrankungen und Lungenkrebs verursachen. Nach Untersuchungen der WHO wurde im Jahr 2000 durch Partikeln die Lebenszeit in der EU25 um 8,6 Monate und in Deutschland um 10,2 Monate verkürzt. Die Weltgesundheitsbehörde, die EU-Kommission sowie der National Research Council und die EPA der USA stellen die Wirkung von Partikeln auf die menschliche Gesundheit als eines der gegenwärtig vorrangigen umwelthygienischen Schwerpunktthemen heraus. Hauptverursacher dieser gesundheitsschädlichen Partikelimmissionen ist der Verkehr. Der Beitrag stellt den Stand der Diskussionen dar, wie der Verkehrsbereich dazu beitragen kann, die Grenzwerte von PM10 einzuhalten, die zum Schutz der menschlichen Gesundheit erlassen worden sind. difu

Long term plans to reduce air pollution - and associated short term action plans - are required to include measures aimed at the polluters involved, in line with the level of their contribution to pollution and according to the principle of proportionality. All modes of transport must be included in the measures proposed since they are the main cause of pollution. Because of this, plans to reduce air pollution - and related short term moves - tend to include traffic guidance measures. Traffic restrictions in the form of blocking lorries' access to selected streets (not cars with a low level of harmful emissions or cars without particles or trucks without particle filters), are resorted to in those instances where traffic planning measures prove inadequate. Appropriate measures, which are permissible and compulsory, are to be adopted by the concerned road traffic authorities. There is no need to resort to the rules of law. The limits imposed by the 22nd BimSchV may enhance the innovation potential in the car manufacturing industry since older cars with low emission may no longer be properly used. Measures aimed at reducing the level of emission, and adopted early on, are known to prove most effective. The acquisition of busses - not fitted out with filter systems - for the ÖPNV (Public Local Passenger Transport) is, therefore, no longer acceptable. It is to be hoped that Germany's car manufacturing industry will again reach a top position worldwide with regard to innovations in the field of environmental technology for the benefit of ordinary citizens and Germany's industry. difu
Keywords: Umweltschutz; Luftverunreinigung; Umweltbelastung; Staub; Kraftfahrzeug; Lastkraftwagenverkehr; Personenkraftwagenverkehr; Gemeinde; Stadtklima; Feinstaub; Staubemission; Luftqualität; Luftreinhaltepolitik; Luftreinhalteplan; Verkehrslenkung; Verkehrsbeschränkung; Abgasemission